Dipeptidyl peptidase III as a DNA marker to investigate epidemiology and taxonomy of Old World Leishmania species. - Insaf Bel Hadj Ali; Hamed Chouaieb; Yusr Saadi Ben Aoun; Emna Harigua-Souiai; Hejer Souguir; Alia Yaacoub; Oussaïma El Dbouni; Zoubir Harrat; Maowia M Mukhtar; Moncef Ben Said; Nabil Haddad; Akila Fathallah-Mili; et al. (Public Library of Science (PLoS), 2021)
Background Dipeptidyl peptidase III (DPPIII) member of M49 peptidase family is a zinc-dependent metallopeptidase that cleaves dipeptides sequentially from the N-terminus of its substrates. In Leishmania, DPPIII, was reported with other peptidases to play a significant role in parasites' growth and survival. In a previous study, we used a coding sequence annotated as DPPIII to develop and evaluate a PCR assay that is specific to dermotropic Old World (OW) Leishmania species. Thus, our objective was to further assess use of this gene for Leishmania species identification and for phylogeny, and thus for diagnostic and molecular epidemiology studies of Old World Leishmania species. Methodology Orthologous DDPIII genes were searched in all Leishmania genomes and aligned to design PCR primers and identify relevant restriction enzymes. A PCR assays was developed and seventy-two Leishmania fragment sequences were analyzed using MEGA X genetics software to infer evolution and phylogenetic relationships of studied species and strains. A PCR-RFLP scheme was also designed and tested on 58 OW Leishmania strains belonging to 8 Leishmania species and evaluated on 75 human clinical skin samples. Findings Sequence analysis showed 478 variable sites (302 being parsimony informative). Test of natural selection (dN-dS) (-0.164, SE = 0.013) inferred a negative selection, characteristic of essential genes, corroborating the DPPIII importance for parasite survival. Inter- and intra-specific genetic diversity was used to develop universal amplification of a 662bp fragment. Sequence analyses and phylogenies confirmed occurrence of 6 clusters congruent to L. major, L. tropica, L. aethiopica, L. arabica, L. turanica, L. tarentolae species, and one to the L. infantum and L. donovani species complex. A PCR-RFLP algorithm for Leishmania species identification was designed using double digestions with HaeIII and KpnI and with SacI and PvuII endonucleases. Overall, this PCR-RFLP yielded distinct profiles for each of the species L. major, L. tropica, L. aethiopica, L. arabica and L. turanica and the L. (Sauroleishmania) L. tarentolae. The species L. donovani, and L. infantum shared the same profile except for strains of Indian origin. When tested on clinical samples, the DPPIII PCR showed sensitivities of 82.22% when compared to direct examination and was able to identify 84.78% of the positive samples. Conclusion The study demonstrates that DPPIII gene is suitable to detect and identify Leishmania species and to complement other molecular methods for leishmaniases diagnosis and epidemiology. Thus, it can contribute to evidence-based disease control and surveillance.